أثر حوكمة الشركات في الحد من ممارسات المحاسبة الإبداعية: دراسة تطبيقية على شركة المياه والصرف الصحي المنطقة الجنوبية - يوسف مصباح علي محمد (Surman Journal of Science and Technology, 2026)
This study aims to examine the impact of corporate governance on reducing creative accounting practices through an applied study on the Water and Wastewater Company in the Southern Region. Corporate governance is considered one of the most important modern mechanisms that enhance transparency, accountability, and the quality of financial reporting, thereby limiting the manipulation of accounting information. The study adopts a descriptive-analytical approach and uses a questionnaire as the main data collection tool targeting a sample of accounting and administrative staff. The findings reveal a significant impact of corporate governance mechanisms—such as audit committees, disclosure, and internal control—in reducing creative accounting practices and improving the credibility of financial statements. The study recommends strengthening governance regulations and promoting ethical and professional awareness among accountants.